2010
DOI: 10.1097/aog.0b013e3181e4bec7
|View full text |Cite
|
Sign up to set email alerts
|

Discordant Blood Chimerism in Dizygotic Monochorionic Laser-Treated Twin–Twin Transfusion Syndrome

Abstract: Despite in utero separation of the fetal circulations remote from delivery, hematologic chimerism persisted after birth. We speculate that the greater degree of blood chimerism in the recipient compared with the donor was related to the pathophysiology of twin-twin transfusion syndrome before laser surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…As in our case, the majority of those described previously have occurred in the context of infertility treatment with ovarian stimulation and artificial insemination i.e. IVF or IVF + ICSI [3,6,8,9,[11][12][13][14]16]. Typically numerous embryos were transferred simultaneously.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…As in our case, the majority of those described previously have occurred in the context of infertility treatment with ovarian stimulation and artificial insemination i.e. IVF or IVF + ICSI [3,6,8,9,[11][12][13][14]16]. Typically numerous embryos were transferred simultaneously.…”
mentioning
confidence: 76%
“…To date 15 cases of monochorionic, dizygotic twins with chimerism have been described [3][4][5][6][7][8][9][10][11][12][13][14]. Most of these cases were blood chimerisms due to twin-twin transfusion in the presence of a common placenta [3,[5][6][7][8][10][11][12][13]; in this case chromosomal analysis of mucosa or skin biopsy is consistent with phenotypic sex. In the current case FISH was carried out on urothelium from both twins.…”
mentioning
confidence: 99%
“…Although various tissues other than blood derived from MCDZTs have been investigated in previous studies, none of these tissues demonstrated chimerism. [1][2][3][4][5] Previous reports thus concluded that chimerism is confined to blood cells and that clinical consequences of chimerism in other tissues would be minimal.…”
Section: Discussionmentioning
confidence: 99%
“…1 Miura et al and Assaf et al hypothesized that the fusion of outer cell masses at the morula stage between 2 eggs might be a cause of monochorionic dizygotes in artificial fertilization. 5,8 In either case, 2 fetuses might reside within close proximity when a single blastocyst with double inner masses is generated. In the present case, some cells derived from the 46,XX fetus could have migrated to the ectoderm of the 46,XY fetus when 2 inner cell masses are within close proximity, which later might have developed into the buccal membrane.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation